Classification Of Inorganic Substances and Their Types (Texas Journal of Multidisciplinary Studies, 2021)
In chemistry, an inorganic compound is typically a chemical compound that lacks carbon–hydrogen bonds, that is, a compound that is not an organic compound. However, the distinction is not clearly defined; authorities have differing views on the subject. The study of inorganic compounds is a subfield of chemistry known as inorganic chemistry